Growth responses of seedlings under complete submergence in rice cultivars carrying both the submergence-tolerance gene SUB1A-1 and the floating genes SNORKELs. (2nd January 2022) - Oe, Shunsuke; Sasayama, Daisuke; Luo, Quanshu; Fukayama, Hiroshi; Hatanaka, Tomoko; Azuma, Tetsushi
ABSTRACT: We screened 80 Asian rice ( Oryza sativa L.) cultivars for the presence of the submergence-tolerance gene SUB1A-1 and the floating genes SNORKEL1 ( SK1 ) and SNORKEL2 ( SK2 ), and found that the deepwater rice cultivar Baisbish (BSB) and the submergence-tolerant cultivar Flood Resistant 13A (FR13A) both possess the SUB1A-1 and the SK1 / 2 . When BSB and FR13A seedlings were completely submerged, spindly growth of shoots was induced in BSB but not in FR13A. Submergence significantly increased the SUB1A-1 transcript abundance in BSB and FR13A shoots, but the expression level in BSB was much lower than that of FR13A. Submergence also induced the expression of both ERF66 and ERF67, the transcriptional targets of SUB1A-1, in FR13A shoots, whereas it upregulated the expression of ERF67 but not that of ERF66 in BSB shoots. These results suggest that BSB could not display submergence tolerance due to the low expression of SUB1A-1 and/or ERF66 under submergence. Graphical abstract: uf0001